2019
DOI: 10.3906/sag-1810-110
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of targeted narrowband UVB therapy: a retrospective cohort study

Abstract: Background/aim: Phototherapy is a safe and effective treatment modality for numerous dermatological conditions. Recently, targeted phototherapy modalities have gained importance due to their advantages over conventional phototherapy. This retrospective study aimed to evaluate the safety and efficacy of targeted narrowband UVB phototherapy in patients with dermatological disorders. Materials and methods: This single-center study included 173 patients who were treated with targeted narrowband UVB phototherapy. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In a retrospective study that investigated the efficacy and safety of NB-UVB therapy in patients with vitiligo, psoriasis vulgaris, lower complete response rates were reported than the present study (6.5% in vitiligo and 8.5% in psoriasis). 8 However in that study complete remission was defined as regression of more than 90% of lesions which may be related to low treatment response.…”
Section: Discussionmentioning
confidence: 95%
“…In a retrospective study that investigated the efficacy and safety of NB-UVB therapy in patients with vitiligo, psoriasis vulgaris, lower complete response rates were reported than the present study (6.5% in vitiligo and 8.5% in psoriasis). 8 However in that study complete remission was defined as regression of more than 90% of lesions which may be related to low treatment response.…”
Section: Discussionmentioning
confidence: 95%
“…Recent data suggest that microfocused NB‐UVB should be considered as the first‐line treatment for localized vitiligo 24 . The main adverse effect is mild erythema 29 . Another variant of this modality is selective sunlight therapy, in which a cream that filters ultraviolet radiation to allow only NB‐UVB to reach the skin is applied on the lesions 13 …”
Section: Phototherapymentioning
confidence: 99%
“…13,29 It allows quick delivery of energy in higher doses, shortening the amount of treatment sessions needed, and achieving a faster response. 29 Besides, it is useful for treating difficult areas (such as the scalp, nose, and genitals). Targeted phototherapy can be considered when <10% of body surface area is affected.…”
Section: Targeted Uvb Phototherapymentioning
confidence: 99%
“…NB-UVB phototherapy resulted in moderate to marked improvement in 73.3% of 16 patients with PPP and a 61.4% reduction in a modified PPPASI. 87 However, UVA phototherapy (both paint PUVA and UVA-1) appears to be superior to UVB phototherapy. 88 A study showed 85.45% reduction in the severity index score with PUVA, compared with 61.03% with NB-UVB.…”
Section: Phototherapymentioning
confidence: 99%